The Role of the Front Nahdliyin to Support Sovereignty over Natural Resources: Hadith Reception on Ecology - Wahyu Saepudin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
The Front Nahdliyin for Sovereignty over Natural Resources (FNKSDA) is an organization concentrated on socio-ecological issues. FNKSDA bases its struggle on religious text, including hadith. Hadith generally recognized as part of an important learning resource in Islamic boarding schools (Pesantren) in Indonesia. This organization uses hadith and traditions of their Pesantren, to organize their ideas, interpretations, and organizational framework. This paper describes FNKSDA's ideas and responds in understanding hadith related to the socio-ecological issues. By using in-depth interview method this article finds that socio-ecological hadith are perceived with a synchronous reception. FNKSDA uses three construction elements in its acceptance theory called general norms. This research also finds some indirect relation between the reception of hadith in the present and in the Prophetic era, without any imaginary contradiction